Simultaneous inhibition of FAK and ROS1 synergistically repressed triple-negative breast cancer by upregulating p53 signalling - Ximin Tan; Deguang Kong; Zhuoli Tao; Fangling Cheng; Baoyuan Zhang; Zaiqi Wang; Qi Mei; Chuang Chen; Kongming Wu (Biomarker Research, 2024)
Abstract Background Triple-negative breast cancer (TNBC) is an aggressive breast cancer subtype lacking effective targeted therapies, necessitating innovative treatment approaches. While targeting ROS proto-oncogene 1 (ROS1) with crizotinib has shown promise, resistance remains a limitation. Recent evidence links focal adhesion kinase (FAK) to drug resistance, prompting our study to assess the combined impact of FAK inhibitor IN10018 and crizotinib in TNBC and elucidate the underlying mechanisms. Methods We employed the Timer database to analyze FAK and ROS1 mRNA levels in TNBC and adjacent normal tissues. Furthermore, we investigated the correlation between FAK, ROS1, and TNBC clinical prognosis using the GSE database. We conducted various in vitro assays, including cell viability, colony formation, flow cytometry, EdU assays, and western blotting. Additionally, TNBC xenograft and human TNBC organoid models were established to assess the combined therapy’s efficacy. To comprehensively understand the synergistic anti-tumor mechanisms, we utilized multiple techniques, such as RNA sequencing, immunofluorescence, cell flow cytometry, C11-BODIPY staining, MDA assay, and GSH assay. Results The Timer database revealed higher levels of FAK and ROS1 in TNBC tissues compared to normal tissues. Analysis of GEO databases indicated that patients with high FAK and ROS1 expression had the poorest prognosis. Western blotting confirmed increased p-FAK expression in crizotinib-resistant TNBC cells. In vitro experiments showed that the combination therapy down-regulated cyclin B1, p-Cdc2, and Bcl2 while up-regulating BAX, cleaved-Caspase-3, cleaved-Caspase-9, and cleaved PARP. In TNBC xenograft models, the tumor volume in the combination therapy group was 73% smaller compared to the control group (p < 0.0001). Additionally, the combination therapy resulted in a 70% reduction in cell viability in human TNBC organoid models (p < 0.0001). RNA sequencing analysis of TNBC cells and xenograft tumor tissues highlighted enrichment in oxidative stress, glutathione metabolism, and p53 pathways. The combined group displayed a fivefold rise in the reactive oxygen species level, a 69% decrease in the GSH/GSSG ratio, and a sixfold increase in the lipid peroxidation in comparison to the control group. Western blotting demonstrated p53 upregulation and SCL7A11 and GPX4 downregulation in the combination group. The addition of a p53 inhibitor reversed these effects. Conclusion Our study demonstrates that the combination of IN10018 and crizotinib shows synergistic antitumor effects in TNBC. Mechanistically, this combination inhibits cell proliferation, enhances apoptosis, and induces ferroptosis, which is associated with increased p53 levels.